2022
DOI: 10.2147/cmar.s382903
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Disparities and Management in Southern Africa: Insights into Practices, Norms and Values

Abstract: Prostate cancer (PCa) is a leading cause of mortality in men of African origin. While men of African descent in highincome countries (HICs) demonstrate poor prognosis compared to their European counterparts, African men on the African continent, particularly Southern Africa have shown even higher PCa mortality rates. Extrinsic factors such as the socioeconomic status, education level, income level, geographic location and race contribute to PCa patient outcome. These are further deepened by the African norms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Various studies have reported on the barriers to PCa screening in Africa, which include lack of patient education, poor uptake in low socioeconomic communities, and lack of resources to implement screening as well as treatment. [2,41] The logistical and resource-related challenges to roll out an effective screening programme would be immense but not insurmountable. Achieving good uptake and participation in such a programme, especially in the black South African male population, will require an in-depth understanding of cultural and gender-specific beliefs within the different communities, especially in rural areas, where these ideas are even more entrenched.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have reported on the barriers to PCa screening in Africa, which include lack of patient education, poor uptake in low socioeconomic communities, and lack of resources to implement screening as well as treatment. [2,41] The logistical and resource-related challenges to roll out an effective screening programme would be immense but not insurmountable. Achieving good uptake and participation in such a programme, especially in the black South African male population, will require an in-depth understanding of cultural and gender-specific beliefs within the different communities, especially in rural areas, where these ideas are even more entrenched.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving good uptake and participation in such a programme, especially in the black South African male population, will require an in-depth understanding of cultural and gender-specific beliefs within the different communities, especially in rural areas, where these ideas are even more entrenched. [2,39] The dearth of urological services to treat increased numbers of PCa patients, especially in the public sector, [42,43] leaves us with ethical questions regarding the initiation of a more robust screening programme. The inevitable increased burden of disease may, on the other hand, place greater focus on the severely under-resourced men's health sector in our country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By focusing on improving diagnostic capabilities, implementing effective screening strategies, and fostering education about the disease, these regions can make significant strides in the battle against prostate cancer. Collaborative efforts are essential to ensure that men across these diverse landscapes have access to the information and healthcare services necessary for the early detection and management of prostate cancer, ultimately improving survival rates and quality of life for those affected by this disease [14] . The aim of study is to evaluate the understanding and stance of physicians in Baghdad regarding prostate cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Black African men have been found to present later with a more advanced stage and higher histological grade at presentation than their non-black counterparts. [2] The incidence of PCa in southern Africa has increased by an estimated 60% in the past decade and a half [3] and could lead to an increase in mortality rates in black African men if the disease is not adequately and timeously managed.Another concern is the disparity in resources for diagnosing and treating PCa at any stage in developing countries, especially African countries, when compared with the developed world. Although Northern and Western Europe have some of the highest PCa incidence rates globally, at the same time they also have very low mortality rates.…”
mentioning
confidence: 99%